Identification of QTLs for rice grain size and weight by high-throughput SNP markers in the IR64 x Sadri population - Aslam, Kashif; Naveed, Shahzad Amir; Sabar, Muhammad; Shabir, Ghulam; Shah, Shahid Masood; Khan, Abdul Rehman; Shah, Muhammad Musaddiq; Fiaz, Sajid; Xu, Jianlong; Arif, Muhammad (Frontiers in Genetics, 2022)
Grain appearance is the most important characteristic of staple crops and grain size, shape and weight are main agronomic traits determining rice yield and market value. In this study QTLs for grain length, grain width, grain length/width ratio and grain weight were mapped using the high-throughput Indica/Indica and Indica/Japonica SNPs platforms. Population of the mega indica variety IR64 and the high quality aromatic variety Sadri from Iran was phenotyped and 94 F2:3 families representing the phenotypic extremes and both parents were genotyped. A linkage map of 210 SNP markers was constructed. Fourteen QTLs were identified, controlling the grain length, grain width, length/width ratio and 1000 grain weight. One major QTL derived from Sadri for decreased length/width ratio and increased grain weight was mapped on chromosome 8, showing effect on all four traits with different phenotypic variance. This study demonstrated the speed and efficiency in using multiplex SNP genotyping for QTL analysis. Moreover, four the novel QTLs (qGL8, qTGW8, qLWR8 and qGW8 ) sharing same position on chromosome 8 were identified for grain quality characters between an indica and aromatic varieties complemented previous indica/japonica QTLs and will enable more precise marker assisted selection for grain weight, shape and size. More studies are required for fine mapping of this QTL to identify gene(s) and to find out in different genetic backgrounds.